Cephalic Index in the First Three Years of Life: Study of Children with Normal Brain Development Based on Computed Tomography - Wirginia Likus; Grzegorz Bajor; Katrzyna Gruszczyńska; Jan Baron; Jarosław Markowski; Magdalena Machnikowska-Sokołowska; Daniela Milka; Tomasz Lepich (The Scientific World Journal)
Cephalic index is a highly useful method for planning surgical procedures, as well as assessing their effectiveness in correcting cranial deformations in children. There are relatively very few studies measuring cephalic index in healthy Caucasian young children. The aim of our study was to develop a classification of current cephalic index for healthy Caucasian children up to 3 years of age with normal brain development, using axial slice computer tomography performed with very thin slices (0.5 mm) resulting in more accurate measurements. 180 healthy infants (83 females and 97 males) were divided into 5 age categories: 0–3, 4–6, 7–12, 13–24, and 25–36 months. The average value of cephalic index in children up to 3 years of age amounted to 81.45 ± 7.06. The index value in case of children under 3 months was 80.19, 4 to 6 months was 81.45, 7 to 12 months was 83.15, in children under 2 years was 81.05, and in children under 3 years was 79.76. Mesocephaly is the dominating skull shape in children. In this study, we formulated a classification of current cephalic indices of children with normal brain development. Our date appears to be of utmost importance in anthropology, anatomy forensic medicine, and genetics.